Cognitive and Affective Mediators of Alcohol-Facilitated Intimate-Partner Aggression. (May 2021) - Eckhardt, Christopher I.; Parrott, Dominic J.; Swartout, Kevin M.; Leone, Ruschelle M.; Purvis, Danielle M.; Massa, Andrea A.; Sprunger, Joel G.
In this multisite study, we examined whether aggressive cognitions and facial displays of negative affect and anger experienced during provocation mediated the association between alcohol intoxication and intimate-partner aggression (IPA). Participants were 249 heavy drinkers (148 men, 101 women) with a recent history of IPA perpetration. Participants were randomly assigned to an alcohol or no-alcohol control-beverage condition and completed a shock-based aggression task involving apparent provocation by their intimate partner. During provocation, a hidden camera recorded participants' facial expressions and verbal articulations, which were later coded using the Facial Action Coding System and the Articulated Thoughts in Simulated Situations paradigm. Results indicated that the positive association between alcohol intoxication and partner-directed physical aggression was mediated by participants' aggressive cognitions but not by negative affect or anger facial expressions. These findings implicate aggressogenic cognitions as a mediating mechanism underlying the association between the acute effects of alcohol and IPA perpetration.